Uma nova espécie de aranha do gênero Matta Crosby do Brasil (Araneae: Tetrablemmidae) (Lundiana: International Journal of Biodiversity, 2005)
Matta angelomachadoi new species from the states of Alagoas and Bahia, Brazil, is described and details of the female internal genitalia are presented. This is the second species of Matta described from South America and it seems to be restricted to the Atlantic Forest in the Brazilian coast.